Growing Pains of Crowdsourced Stream Stage Monitoring Using Mobile Phones: The Development of CrowdHydrology - Lowry, Christopher S.; Fienen, Michael N.; Hall, Damon M.; Stepenuck, Kristine F. (Frontiers in Earth Science, 2019)
Citizen science-based approaches to monitor the natural environment tend to be bimodal in maturity. Older and established studies such as the Audubon’s Christmas bird count and Community Collaborative Rain, Hail and Snow Network (CoCoRaHS) have thousands of participants across decades of observations, while less mature citizen science projects have shorter lifespans often focused on local or regional observations with tens or hundreds of participants. For the latter, it can be difficult to transition into a more mature and sustainable citizen science-based research project. This research focuses on this transition by evaluating CrowdHydrology (ca. 2010), a citizen science project that has transitioned from a regional to national network. The CrowdHydrology network asks citizens to send in text messages of water levels in streams and lakes, which has resulted in 16,294 observations submitted by over 8,000 unique participants. Using water level data and participation records from CrowdHydrology, we evaluate the expansion and citizen participation from a regional to national citizen science initiative. We identify barriers to entry to participation and evaluate why some citizen science observation stations are popular while others are not. We explore our chosen contributory program model for CrowdHydrology and the influence this model has had on long-term participation. Results demonstrate a highly variable rate of contributions of citizen scientists and address why many of our observations are from one-time participants. Finally, we address the future expansion of the CrowdHydrology network by evaluating current successful monitoring locations and recent expansion of interest from watershed groups to participate in the project.